Coping with Pleistocene climatic fluctuations: Demographic responses in remote endemic reef fishes. Issue 12 (13th June 2020) - Delrieu‐Trottin, Erwan; Hubert, Nicolas; Giles, Emily C.; Chifflet‐Belle, Pascaline; Suwalski, Arnaud; Neglia, Valentina; Rapu‐Edmunds, Cristian; Mona, Stefano; Saenz‐Agudelo, Pablo
Abstract: Elucidating demographic history during the settlement of ecological communities is crucial for properly inferring the mechanisms that shape patterns of species diversity and their persistence through time. Here, we used genomic data and coalescent‐based approaches to elucidate for the first time the demographic dynamics associated with the settlement by endemic reef fish fauna of one of the most remote peripheral islands of the Pacific Ocean, Rapa Nui (Easter Island). We compared the demographic history of nine endemic species in order to explore their demographic responses to Pleistocene climatic fluctuations. We found that species endemic to Rapa Nui share a common demographic history, as signatures of population expansions were retrieved for almost all of the species studied here, and synchronous demographic expansions initiated during the last glacial period were recovered for more than half of the studied species. These results suggest that eustatic fluctuations associated with Milankovitch cycles have played a central role in species demographic histories and in the final stage of the community assembly of many Rapa Nui reef fishes. Specifically, sea level lowstands resulted in the maximum reef habitat extension for Rapa Nui endemic species; we discuss the potential role of seamounts in allowing endemic species to cope with Pleistocene climatic fluctuations, and we highlight the importance of local historical processes over regional ones. Overall, our results shed light on the mechanisms by which endemism arises and is maintained in peripheral reef fish fauna.